PENGARUH STRATEGI E-COMMERCE DALAM PENGEMBANGAN UMKM TERHADAP PENINGKATAN PROFITABILITAS DI DESA KALIWULU - Ad. Silvia Ade (Jendela ASWAJA, 2023)
Abstract E-Commerce offers in its use to improve production marketing strategy. One government agency that has implemented an E-Commerce strategy is Kaliwulu Village, which is located in Plered District. This study aims to determine the effect of the E-Commerce strategy, to determine the development of MSMEs and to determine the increase in profitability of Kaliwulu Village. The research method in this study is descriptive descriptive. The data collection used was by distributing questionnaires accompanied by observation techniques. Data analysis technique using Multiple Linear Regression Analysis. The results showed that the E-Commerce Strategy in MSME Development had a significant effect on Increasing Profitability by 60.2%, the remaining 39.8% was influenced by other factors.